Generating Correctness-Preserving Editing Operations for Diagram Editors - Mazanek, Steffen; Minas, Mark (Electronic Communications of the EASST, 2009)
In previous work it has already been shown that syntax-directed and free-hand editing can be gainfully integrated into a single diagram editor. That way, the user can arrange diagram components on the screen without any restrictions in free-hand editing mode, whereas syntax-directed editing operations provide powerful assistance. So far, editing operations had to be specified or programmed by the editor developer. In contrast, this paper proposes an approach where diagram-specific editing operations are generated on the fly during the editing process and without any additional specification effort. These operations provably preserve the correctness of the diagram. The proposed approach requires a specification of the visual language by a hypergraph grammar.